The eﬀectiveness of capacitive and resistive electric transfer therapy for nonspeciﬁc chronic low back pain: a systematic review - Ismail, Shumaila; Usa, Hideyuki; Nidhya, Krishnamoorthy (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Introduction. Capacitive and resistive electric transfer (CRET) therapy is widely used for the treatment of musculoskeletal dis-orders, including chronic low back pain (CLBP). However, the eﬀects of CRET on nonspeciﬁc CLBP remain unexamined. Therefore, this systematic review aimed to investigate the eﬀectiveness of CRET therapy for 3 months nonspeciﬁc CLBP.Methods. Six electronic databases (PubMed, Embase, PEDro, MEDLINE, Scopus, and Cumulative Index to Nursing and Allied Health Literature) were systematically searched for relevant literature. The quality of the included studies was assessed using PEDro scores. Furthermore, a risk-of-bias analysis was performed using the Cochrane tool for risk-of-bias assessment.Results. Seven randomized controlled trials were included in this analysis, with 351 participants aged 18–70 years. CRET was compared with manual therapy, other modalities, or sham CRET (power oﬀ). Several devices, including Physio Radio Stim Pro, INDIBA Active Pro recovery HCR 902, and WinBack-TECAR, were used for CRET therapy. These ﬁndings indicate that CRET is an eﬀective treatment option for immediate and long-term follow-up of pain reduction and improved physical function in pa-tients with nonspeciﬁc CLBP.Conclusions. This review is the ﬁrst attempt to aggregate and synthesize evidence for the eﬀectiveness of CRET therapy for nonspeciﬁc CLBP. The ﬁndings reveal that CRET therapy is eﬀective for managing nonspeciﬁc CLBP. More randomized con-trolled trials are expected to be conducted in the future that will strengthen the evidence on the eﬀectiveness of CRET for non-speciﬁc CLBP.
Keywords: capacitive and resistive electric transfer therapy; low back pain; radiofrequency; thermotherapy